2019
DOI: 10.1038/s41598-019-42148-3
|View full text |Cite
|
Sign up to set email alerts
|

µSpikeHunter: An advanced computational tool for the analysis of neuronal communication and action potential propagation in microfluidic platforms

Abstract: Understanding neuronal communication is fundamental in neuroscience, but there are few methodologies offering detailed analysis for well-controlled conditions. By interfacing microElectrode arrays with microFluidics (μEF devices), it is possible to compartmentalize neuronal cultures with a specified alignment of axons and microelectrodes. This setup allows the extracellular recording of spike propagation with a high signal-to-noise ratio over the course of several weeks. Addressing these μEF devices, we develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Avalanches were detected according to the method described by Beggs and Plenz [12]. Spikes were detected using a simple thresholding method [20] based on the standard deviation of the noise of the signal after applying a bandpass filter with a pass band of 300 Hz to 3 kHz 1 . The spike detection threshold was set to 6, 7, and 8 standard deviations below the median of the signal for the cortical networks, and the results were compared to assess the effect of the detection threshold on the classification results.…”
Section: B Avalanche Analysismentioning
confidence: 99%
“…Avalanches were detected according to the method described by Beggs and Plenz [12]. Spikes were detected using a simple thresholding method [20] based on the standard deviation of the noise of the signal after applying a bandpass filter with a pass band of 300 Hz to 3 kHz 1 . The spike detection threshold was set to 6, 7, and 8 standard deviations below the median of the signal for the cortical networks, and the results were compared to assess the effect of the detection threshold on the classification results.…”
Section: B Avalanche Analysismentioning
confidence: 99%
“…Although recordings of random DRG cultures have been previously demonstrated (Black et al, 2019), these are not adapted to the study of peripheral innervation. Here, we employed microElectrode-microFluidic (μEF) devices (Figure 7A), which allowed us to monitor axonal activity with great fidelity (Figure 7B) (Heiney et al, 2019; Lopes et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Then, treatments and recordings were performed at 6-7 DIV. This time point was chosen following preliminary studies that showed adequate electrophysiological maturation and culture viability at this stage (Heiney et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…It is important to note that no study has previously attempted to characterize the signal conduction of DRG cultures (Black et al, 2019). Still, preliminary in vitro experiments using DRGs had suggested that most APs propagate orthodromically (Heiney et al, 2019). Our data shows clearly that bidirectional axonal conduction (EAP initiation/antidromic conduction in particular) must be considered when analyzing functional data from both hippocampal and DRG cultures.…”
Section: Discussionmentioning
confidence: 99%
“…The polydimethylsiloxane (PDMS) microfluidic chambers used in this study followed a design reported on our previous publications (Heiney et al, 2019; Lopes et al, 2018), with minor optimizations regarding the number of microchannels, as well as their length and width. The number of microchannels was reduced to match exactly the number of microelectrode columns (16 microchannels in total).…”
Section: Methodsmentioning
confidence: 99%